Kontribusi Usaha Pengolahan Sagu Terhadap Pendapatan Keluarga di Kampung Tola Kecamatan Tabukan Utara - Mareta Damalang; Theodora M. Katiandagho; Tommy F. Lolowang; Jean F.J. Timban (Universitas Sam Ratulangi, 2014)
ABSTRACTMareta Damalang. Sago Processing Contribution to the Family Income in Tola Village NortTabukan sub District, Under guardance of Th. M. Katiandagho as a Chairman, T. Lolowang and J. Timban as Members.The Objective of this research is to determine contribution of sago processing to the family income in Tola Village northenTabukan district.This study use survey method The data used are primary data and secondary data. Primary data is obtained by direct interviews with farmer and analyzed descriptively, and secondary data is obtained from related institution.The result of this research showed that the contribution of sago processing to the family incomewas 75,00 %, other income (Civil Servants, construction, workers, drivers) was 17,67 % , coconut and nutmea farm income was 21,97 %The conclusion of this research result is sago processing still dominant compared to the other business.